Planejamento de uso e ocupação do solo visando o manejo sustentável das águas pluviais - Perius, Carla Fernanda (2022)
The land use planning in urban areas is a legal instrument that guides the cities development, normally presented as a Land Use/Cover Plan (LUCP) and has direct consequences in many urban infrastructure services, such as urban stormwater drainage. Urban land use planning is considered as a non-structural measure for the stormwater management, and should be designed to prioritize the maintenance of natural hydrological processes. However, the inclusion of hydrological criteria in LUCP is not common in Brazil. Thus, in this research, it was evaluated the urban land use planning effect in the urban stormwater drainage networks demands, through the analysis of different scenarios that consider strategies for the urban land use organization, according to the watershed physiographic characteristics. By the different scenarios it was possible to identify: i) how the spatial location of the different urban land use, including verticalization and/or horizontalization, affects the stormwater; ii) how the spatial location of the different land use guidelines affects the runoff in the watershed iii) how the different land use guidelines can be combined to guide the runoff reduction and reduce the need for urban drainage infrastructure. For this purpose, the Arroio Cancela watershed located in the Santa Maria – RS was used as a reference, which presents common problems of urban watershed from different regions and possess necessary information for this study. The investigation was performed out by through hydrological-hydraulic numerical modeling by using the Storm Water Management Model (SWMM). The Arroio Cancela watershed was subdivided into sub-watersheds and the network was represented by segments, to seek better routing process adjusts and to better represent the evaluated scenarios. The analysis also contemplated the proposed scenarios simulations for different precipitation events. The hydrographs, maximum flows analysis and total volumes drained were used as scenarios indicators and evaluated at different scales, which include outlets of some sub-watershed, interest points along the drainage channel and the watershed outlet, allowing the verification of the progressive increase effect in the drainage area and of the urbanization on flows and volumes. As results, verticalization processes are beneficial to stormwater urban drainage, since they generate less impervious areas, decreasing maximum flow by until 300% and total volumes drained by until 65%. Verticalizing the steeper regions or those with more permeable soils has also proven to be more beneficial, since they reduce total volumes and the peak flows due to infiltration processes that delay the runoff, acting as a natural retention. The results of this investigation made it possible to draw guidelines for the improvement of the criteria used in the elaboration/review of municipals LUCP, to promote convergence between urban land use zoning towards the sustainable stormwater management in the watershed.